EKSISTENSI BRAND COMMUNITY DI ERA KONVERGENSI: STUDI KASUS BRAND COMMUNITY KEJAR MIMPI OLEH BANK CIMB NIAGA DI ERA KONVERGENSI - Putri, Aprilian; Suryana, Asep; Octavianti, Meria (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
In the current media convergence era, businesses must be agile to remain in their industries and compete with competitors. One of the most promising strategies is brand community, which helps strengthen connection with customers. One of the businesses that has managed to keep up a brand community since 2017 is Bank CIMB Niaga. The focus of this research is to explore how Bank CIMB Niaga's brand community has grown also how the differences in communication messages through community activities and the official account @kejarmimpi.id on Instagram. To ascertain the variations in message depending on the central route and peripheral route, this study applies the Elaboration Likelihood Model theory. The method used is quantitative with a case study approach with data collection techniques through observation and documentation. The results of the study show that brand community packages messages with an emphasis on the central route on community activities that pay attention to the quality of the message and its relevance to the audience. On the other hand, brand community packages messages with an emphasis on the peripheral route on content shared on Instagram social media where it pays more attention to the attractiveness of content writing and the attractiveness of a Key Opinion Leaders (KOL). Overall, this study shows that CIMB Niaga's brand community can still exist because it has succeeded in packaging messages effectively by considering the audience's elaboration rutes.